2020
DOI: 10.18231/2394-6776.2018.0056
|View full text |Cite
|
Sign up to set email alerts
|

Demographic profile of autopsy in Indore region - One year prospective study

Abstract: The term 'Autopsy' originates from ancient 'Autopsia' which is derived from 'Autos' i.e. 'Oneself' and 'Opsis' i.e. 'to see for oneself'. Medico-legal postmortem examinations are performed as mandatory legal procedures for establishing the cause of death for people dying in circumstances where multiple causes of death could be ascribed. The present prospective study was carried out in the Department of Forensic Medicine & Toxicology, M.G.M. Medical College & M.Y. Hospital, Indore during the period from 1st Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
2
1
0
Order By: Relevance
“…in the study. Similar findings were obtained by Rahul Agarwal et al in Indore 3 and by Khaja Azizuddin Junaidi et al in Belgavi. 4 Maximum cases (41) were from 21 to 30 years age group, followed by 31 to 40 (33 cases) and 41 to 50 (16 cases).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…in the study. Similar findings were obtained by Rahul Agarwal et al in Indore 3 and by Khaja Azizuddin Junaidi et al in Belgavi. 4 Maximum cases (41) were from 21 to 30 years age group, followed by 31 to 40 (33 cases) and 41 to 50 (16 cases).…”
Section: Discussionsupporting
confidence: 90%
“…4 Maximum cases (41) were from 21 to 30 years age group, followed by 31 to 40 (33 cases) and 41 to 50 (16 cases). Rahul Agarwal et al in Indore 3 and by Khaja Azizuddin Junaidi et al in Belgavi 4 also found similar results. Amongst males and females it was also the age group of 21 to 30 years which showed maximum cases, 27 and 14 respectively.…”
Section: Discussionmentioning
confidence: 52%
“…This finding of a preponderance of R.T.A.s amongst medicolegal autopsies is not in agreement with studies reported from some parts of India. 17,18,31 The occurrence of suicidal and homicidal fatalities in our study wascomparable to those in other parts of India 20,29. This was true for cases seen in Norway as well, 29 but not in Great Britain and Libya,where suicides were low and homicidal deaths were greater in Libya, where it was twenty percent as contrasted to our 2.7%. 28 The occurrence of unnatural deaths was quite comparable to trends reported from various parts of India and globally.…”
Section: Discussionsupporting
confidence: 50%